Using concept mapping to improve the reading ability - Jaya, Candra; Latief, Mohammad Adnan (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
The objective of this study is to develop a concept mapping strategy to improve the reading ability of second-semester students at the College of Islamic Studies Ma’arif (STAI) Metro–Lampung. A classroom action research design was conducted in two cycles, each comprising planning, implementing, observing, and reflecting. Observation sheets, field notes, interviews, and tests were used during each cycle. The findings reveal that the concept mapping strategy, which involves using a concept mapping format completed based on comprehension of reading texts, successfully improved the reading ability of second-semester students in the English Department at STAI Ma’arif Metro Lampung. This success is indicated by improvements in students’ reading scores and more joyful learning interactions. The students enjoyed learning reading through concept mapping and found the strategy helpful. All students achieved scores above the passing grade of 60 in Cycle 2.